A comparative study of three liquid platelet concentrates on human primary osteoblast activity: an in vitro study - Vichuda CHATTRATHIKUL; Putida PINTHONGLOR; Chayarop SUPANCHART; Supatra SANGIN (Journal of Applied Oral Science)
Abstract Objective: To investigate the effects of concentrated platelet-rich fibrin (C-PRF), injectable platelet-rich fibrin (i-PRF), and platelet-rich plasma (PRP) on cellular activity of human primary osteoblasts. Methodology: C-PRF, i-PRF, and PRP were prepared from five donors and pre-cultured in 5 mL of culture medium for three days. Human primary osteoblasts were seeded and cultured with 20% conditioned medium derived from the three platelet concentrates. Then, osteoblast viability was assessed at 24 h; proliferation at one, three, and five days; differentiation at seven days; mineralization at 14 days; and gene expression RUNX family transcription factor 2 (RUNX2), alkaline phosphatase, biomineralization associated (ALPL), collagen type I alpha 1 chain (COL1A1), and osteocalcin (OCN) at three and 14 days were investigated. Results: Osteoblasts cultured with C-PRF, i-PRF, and PRP demonstrated excellent biocompatibility. Proliferation was significantly higher in all platelet concentrates compared to the controls at one, three, and five days, with no significant differences among them, except on day one. Alkaline phosphatase and Alizarin Red S staining were significantly higher in the C-PRF and i-PRF groups compared to the PRP and control groups. However, RUNX2, ALPL, COL1A1, and OCN mRNA levels did not differ significantly among the three platelet concentrates throughout the study period. Conclusion: Our study indicates that the three liquid platelet concentrates enhance human osteoblast activity. C-PRF and i-PRF promoted greater differentiation and mineralization than PRP. These findings show that all liquid platelet concentrates positively influence human osteoblast proliferation and differentiation, making them suitable for clinical applications requiring bone regeneration.